Pengukuran Laju Paparan Radiasi Pada Ruang Pesawat Konvensional Di Instalasi Radiologi RSUP Dr Tadjuddin Chalid Makassar - Normawati, Sitti; Rustiah, Waode; Ansar, Asnaeni; Harun, Herlinda Mahdania; Aryanto, Bambang; Fajriah, Nur (Madu : Jurnal Kesehatan, 2023)
The purpose of writing to find out how the value of radiation exposure rate in the convensional room at the radiology installation of Dr Tadjuddin Chalid Makassar sentral general hospital.This research was conducted at installation of Dr Tadjuddin Chalid Makassar sentral general hospital 2020/2021 with descriptive method.the operational space Radiology of Dr Tadjuddin Chalid Makassar sentral general hospita is obtained is ≤ 10 mGray / hour then the convensional room space Radiologyif you look at the exposure tolerance limit 10 mGray / hour from the dose limit value provisions 20 mGray/ year is categorized as safe for workers and the environment The rate of radiation exposure in.